Psychological wellness, yoga and quality of life in patients affected by schizophrenia spectrum disorders: A pilot study - Pasquale Caponnetto; Roberta Auditore; Marilena Maglia; Stefano Pipitone; Lucio Inguscio (Mental Illness)
Schizophrenia is a serious psychiatric disorder characterized by positive symptoms, negative symptoms and neurocognitive deficits. The aim of this study was to estimate relationships between wellness, yoga and quality of life in patients affected by schizophrenia spectrum disorders. Participants were 30 patients with a diagnosis of schizophrenia in care at the Rehabilitative Psychiatry and Research Villa Chiara Clinic in Mascalucia (Catania, Italy), after that randomly assigned to two groups. The first group followed the experimental treatment with sets of yoga exercises conducted by a yoga trainer and a psychiatrist or a clinical psychologist expert in yoga, while a second control group was treated with usual care. The results revealed a significant difference, before and after treatment, between the experimental group and the control group in quality of life.